Back on track: Approaches to managing highly disruptive school classes - Grete S. Vaaland (Cogent Education, 2017)
Teaching and learning are at stake when classrooms become highly disruptive and pupils ignore the teacher’s instructions and leadership. Re-establishing teacher authority in a highly disruptive school class is an understudied area. This instrumental multiple case study aimed to reveal concepts and conceptual frameworks that are suitable for describing, analysing and discussing interventions in highly disruptive school classrooms. The tentative conceptual framework for turnarounds in highly disruptive classrooms revealed two main strategies: (1) a cognitive strategy appealing to pupils’ rationality and responsibility, which involves creating an awareness among students about preferred learning environments and training them to obtain the skills needed to behave in accordance with the chosen standards; (2) a systems strategy addressing the class as a social system in which the teacher’s loss of authority has become beneficial to some pupils. Re-establishing teacher authority implies a power takeover by teachers, and success depends on leadership by use of social dynamics. The data cover seven cases, each based on an experienced practitioner’s model for helping highly disruptive classes get back on track. The seven informants had worked as external experts in schools that had given up on coping with classes in which teachers had lost control.